Personal Finance - J.Hughes Robert (Mc Graw Hill, 2008)
Kapoor/Dlabay/Hughes’ Personal Finance is the #1 market-leading Personal Finance text. It provides comprehensive coverage of personal financial planning in the areas of money management, career planning, taxes, consumer credit, housing and other consumer decisions, legal protection, insurance, investments, retirement planning, and estate planning. The goal of this text is to teach students the fundamentals of financial planning so they can make informed choices related to spending, saving, borrowing, and investing that lead to long-term financial security. Personal Finance, Ninth Edition provides many financial planning tools using a step-by-step approach to help students identify and evaluate choices as well as understand the consequences of decisions in terms of opportunity costs.